MENDUGA POTENSI PRODUKSI KAYU BULAT DARI HUTAN KALIMANTAN TIMUR MENGGUNAKAN METODE PENDUGAAN NISBAH DAN PENDUGAAN REGRESI - Han Roliadi; Buharman Buharman (Jurnal Penelitian Hasil Hutan, 1985)
For predicting   the roundwood   potential   in the  forest  region  of  East Kalimantan, roughly  two  kinds  of data are required.  These includes sample  data and population   data.  Sample  data collected are the area or size of several selected  forest region  and  the volume  of  the  corresponding   roundwood   production,    while population   data  include  the  total  forest  area of  East  Kalimantan.The prediction methods  applied are ratio estimate  and regression estimate. Using ratio estimate, the volume  of roundwood  production   potential  predicted was 8 093 575  cu.m  (7 032  723  to 9  154  427  cu.m).   On the other  hand,  with  the application of  regression  estimate, the  uolume  of  roundwood  production   potential   was 8 505  603  cu.m.   (7 889  057  to 9 122 149  cu.m.).Examination of  the  residuals indicated that  assumption of  normality of  data was satisfied